Diabetic ketoacidosis, a one year analysis - Đorđević, Milan (Halo 194 Scientific Journal of Emergency Medicine, 2022)
Diabetic ketoacidosis (DKA) is a common and most severe acute complication of diabetes, with a high morbidity rate and a severe metabolic disorder.The aim of the work. Examine patients hospitalized for DKA and analyze their parameters. The retrospective study included 63 patients with DKA. Data from the protocol of Clinic for Endocrinology Nis, and medical history of the patients were used.The following results were obtained: the number of male patients 31.74%, with average age 56,25 years and female 68,26%, average age 49,75 years, with total average of 53.71 years. Average glycemic values on admission were 24.36 mmol / l; pH 7.14; bicarbonates 11.2. Duration of diabetes was 15.2 years; there were 53,97% of type 2 diabetes patients and 46.03% of type1; duration of hospitalization approximately 7.89 days. The required time for resolving ketoacidosis is 16.21hours. The time required for the administration of GIP (glucose, (insulin) and potassium) solution in the therapy is 4.88 hours. Glycemia when switching on to GIP solution is 10.9 mmol / l. The most common precipitating factor entering DKA is infection 48.32%, followed by absence of insulin in therapy 43.13%, while other causes are 8.55%.Conclusion: We use modern therapeutic algorithms in the approach of patients with ketoacidosis. Our one year follow up showed how patients with DKA were treated and what were their characteristics. Since the diabetes is on the rise, its complications are on the rise, as well, and therefore the prevention is much-needed.
Keywords: Ketoacidosis; acid-base status; diabetes; parameters; electrolytes